2017
DOI: 10.2172/1480122
|View full text |Cite
|
Sign up to set email alerts
|

Landau Damping with Electron Lenses in Space-Charge Dominated Beams

Abstract: Progress on the Intensity Frontier of high energy physics critically depends on record high intensity charged particles accelerators. Beams in such machines become operationally limited by coherent beam instabilities, particularly enhanced in the regime of strong space charge (SC). Usual methods to control the instabilities, such as octupole magnets, beam feedback dampers and employment of chromatic effects, become less effective and insufficient. In [1] it was proposed to employ electron lenses for introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Electron lenses may also be helpful in low-energy high-brightness accelerators, where Landau damping is intrinsically suppressed by a shift of single particle tunes away from the frequency of coherent oscillations [30]; a preliminary study of this issue is suggested in Ref. [31].…”
Section: The Initial Amplitudesmentioning
confidence: 99%
“…Electron lenses may also be helpful in low-energy high-brightness accelerators, where Landau damping is intrinsically suppressed by a shift of single particle tunes away from the frequency of coherent oscillations [30]; a preliminary study of this issue is suggested in Ref. [31].…”
Section: The Initial Amplitudesmentioning
confidence: 99%
“…Similar practical proposals considered a hollow bi-Gaussian electron lens (see Fig. 2a, no.5) as the nonlinear element for creating a tunespread for Landau damping in the 8 GeV proton Recycler storage ring [71] and in the space-charge dominated high intensity beams [72].…”
Section: S: Rhic Electron Lenses Other Experiments Proposals and Ideasmentioning
confidence: 99%
“…For example, within the parameters of the Future Circular Collider (FCC-hh), a single few meters long conventional electron lens would provide stabilization superior to tens of thousands of superconducting octupole magnets. Similar practical proposals considered a hollow bi-Gaussian electron lens (see figure 2a, no.5) as the nonlinear element for creating a tunespread for Landau damping in the 8 GeV proton Recycler storage ring [75] and in the space-charge dominated high intensity beams [76].…”
Section: Jinst 16 P03039mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies presented in refs. [85,86] predicted that there are regimes for which Landau damping with electron lenses, described in section 2.3, is effective under space-charge conditions as well. Experiments with protons in IOTA could shed light on this topic, with a significant impact on the performance of high-intensity accelerators.…”
Section: Other Advanced Studies Of Beam Dynamics and Stabilitymentioning
confidence: 99%